Backbone Distribution Network Design for the Mexican Automotive Industry - Retana-Blanco, Brenda; Marmolejo Saucedo, José Antonio; Rodríguez Aguilar, Román; Pedraza-Arroyo, Erika (My University, 2020)
The logistics network of an automotive company in Mexico was analyzed to propose a better logistics network in the country to improve delivery times to customers. The analysis was conducted with Greenfield Analysis and Network Optimization. Taking into account the information given by the company, it was possible to obtain optimal scenarios for better operation, which involved the construction of distribution centers in the Hidalgo state in Mexico. © Springer Nature Switzerland AG 2020.
Keywords: Supply chain design; Network optimization; Dynamic simulation